Academic work-integrated learning (WIL): Reengaging teaching-focused academics with industry - Michael B. Whelan (Journal of Teaching and Learning for Graduate Employability, 2017)
There has been an increase in the number of teaching-focused academics at Australian universities over recent years. However, research-focused and teaching-research academics have an advantage over teaching-focused academics in terms of promotion, forced redundancies and tenure. While evidence of research success is measured by volume (number of publications and research income), evidence of teaching scholarship is less quantifiable. The value of industry-university collaboration has been reported widely. However, the focus is on the value of the knowledge transfer of university research to industry and collaborative industry-university research. Academics collaborating with industry partners on research projects are able to experience current industry practice firsthand, raising the question: How do teaching-focused academics remain engaged with industry? The benefits of work-integrated learning (WIL) to hosts, students and universities are well documented. This paper poses the question: Is a WIL placement a way to reengage teaching-focused academics with industry?, and introduces the concept of ‘Academic WIL’ where academics complete an internship placement with an industry partner. The impact on graduate employability is discussed and a methodology for a teaching-focused academic to use their Academic WIL experience as evidence of their achievements in the scholarship of teaching is presented.